Antimicrobial Activity of Ethanol Extract of Cucumber (Cucumis Sativus L.) Peels and Formulation as Anti-Acne Cream - Nadya Wulan Ramadhani; Siti Harnina Bintari (Journal of Science and Technology Research for Pharmacy, 2023)
Background: Cucumber is proven to have pharmacological activities as antimicrobial. Some of the secondary metabolites contained in cucumber fruit have antimicrobial activity. Aim: This study aims to determine the antibacterial activity of ethanol extract of cucumber peels against Staphylococcus epidermidis and to make anti-acne cream using cucumber skin extract. Material and Methods: The extraction of cucumber peels extract with maceration using 96% ethanol solvent. Phytochemical screening to determine the compounds contained in the extract. The antibacterial activity test of the extract was carried out through liquid and solid dilution methods to determine the MIC and MBC values. The extract was then made into a cream with varying concentrations of stearic acid and TEA as an emulsifier and then evaluated and tested for antibacterial activity using the agar diffusion method. Results: Cucumber peels extract contains steroids, alkaloids, flavonoids, phenols, and saponins that have antibacterial activity against Staphylococcus epidermidis with an MIC value of 2.5% and an MBC value of 5%. The results of the cream evaluation test show that formula F(3) is the most optimal formula for inhibiting Staphylococcus epidermidis bacteria with a cucumber skin concentration content of 4.5%. The antibacterial activity test has an inhibition zone of 33-52.70 mm with a very strong category.